TRPC3 contributes to cyclophosphamide-induced cystitis progression by enhancing bladder fibrosis through activation of the TGF-β/smad pathway - Luo, Ruixiang; Li, Wenshuang; Huang, Junlong; Liu, Zheng; Zhang, Chi; Ding, Honglu; Chen, Jialiang (Frontiers in Pharmacology, 2025)
BackgroundBladder pain syndrome/Interstitial cystitis (BPS/IC) is a chronic urological disorder affecting 2.7%–6.5% of the population. The condition is characterized by significant bladder-related pain, with approximately 50% of IC/BPS patients exhibiting bladder fibrosis. Transient receptor potential cation channel subfamily C member 3 (TRPC3), a protein linked to fibrosis in heart and kidneys, emerged as a potential therapeutic target for this condition.MethodsUsing a cyclophosphamide-induced cystitis rat model, we employed RNA sequencing for transcriptional profiling, Western blot for protein quantification, and Masson staining for fibrotic assessment. Cellular-specific TRPC3 expression patterns were elucidated through single-cell transcriptomic analysis. TRPC3 inhibition was implemented via intraperitoneal administration of Pyrazole 3. The study assessed mechanical pain sensitivity and bladder function through von Frey testing and cystometry.ResultsSignificant findings revealed TRPC3 RNA and protein expression was markedly upregulated in cystitis rats. TRPC3 inhibition substantially improved mechanical pain sensitivity and reduced micturition frequency. TRPC3 is predominantly expressed in fibroblasts and fibrosis-related pathways are upregulated in cystitis rats. The increased fibrosis markers and collagen fiber deposition are both reversed by TRPC3 inhibition. And the TGF-β/Smad signaling pathway was notably activated and subsequently downregulated with TRPC3 inhibition.ConclusionTRPC3 activation contributes significantly to bladder fibrosis in IC/BPS. Inhibiting TRPC3 ameliorates symptoms by modulating TGF-β/Smad pathway, suggesting it as a promising therapeutic target for managing this challenging condition with limited current treatment options.